the Eau Claire Investment Basket : an Analysis of Local Stock Performance 2008-2009. - Tessmer, Ryan; Brueggen, Alex; Ziemann, Ben; Trow, Alex; Hennick, David (My University, 2009)
Our research poster examines the stock market in 2008 and compares this tough year to other recent years. We look at 51 stocks with a local employment presence in the Eau Claire area to see how these companies fared in 2008 as compared to the overall all market trends.
Color poster with text and graphs (Spring 2009)
Keywords: Posters; Stocks--Wisconsin--Eau Claire; Stocks--Charts, diagrams, etc.; Stock price indexes; Investments--Wisconsin--Eau Claire